A Malaria Model with Two Delays. (10th March 2013) - Wan, Hui; Cui, Jing-an
Abstract : A transmission model of malaria with two delays is formulated. We calculate the basic reproduction number R 0 for the model. It is shown that the basic reproduction number is a decreasing function of two time delays. The existence of the equilibria is studied. Our results suggest that the model undergoes a backward bifurcation, which implies that bringing the basic reproduction number below 1 is not enough to eradicate malaria.